Reinterpretasi Gagasan Moderasi Beragama Kacamata Al-Qur'an sebagai Upaya dalam Mewujudkan Kedamaian di Indonesia - Muhamad Yoga Firdaus; Faisal Salistya; Moh. Romli; Muhammad Rizal Arsyad (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This research is presented to explore the idea of ​​religious moderation from the perspective of the Qur'an for the sake of creating peace in Indonesia. On this occasion, the author uses a qualitative method with a literature study through a thematic or maudhu'i approach. This research includes a discussion of Islam and religious moderation, verses related to religious moderation, and the idea of ​​religious moderation from the perspective of the Qur'an as an effort to create peace in Indonesia. This research simply results in the conclusion that Islam guides every Muslim, especially in Indonesia through the Qur'an by advocating for upholding the spiritual values ​​and human values ​​for the sake of creating peace in Indonesia. This study only describes the idea of ​​religious moderation from the perspective of the Qur'an through thematic studies only. Then, this study recommends that in the future a more up-to-date understanding of the idea of ​​religious moderation can be generated through a comprehensive study or tahlili referring to the literature on the interpretation of the Qur'an in particular.